2022
DOI: 10.1002/cpp.2765
|View full text |Cite
|
Sign up to set email alerts
|

The ICD‐11 and DSM‐5‐TR prolonged grief criteria: Validation of the Traumatic Grief Inventory‐Self Report Plus using exploratory factor analysis and item response theory

Abstract: More recently, the prolonged grief disorder (PGD) has been recognized as a mental health disorder following bereavement, which is distinct from depression and PTSD. However, the number and proposed symptom items vary across the ICD‐11 and the DSM‐5‐TR criteria for PG. The Traumatic Grief Inventory‐Self Report Plus (TGI‐SR+), which is an updated version of the TGI‐SR, is currently the only robust instrument that assesses PG according to the ICD‐11 and DSM‐5‐TR criteria. For research and clinical use among Frenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 55 publications
4
4
0
Order By: Relevance
“…These study characteristics may limit the generalizability of our findings to other groups of bereaved adults. However, it should be noted that the results found in the present study were comparable to the results of past validation studies using different samples (Kokou‐Kpolou et al, 2022; Lenferink et al, 2022), which appears to suggest that the TGI‐SR+ has similar psychometric properties across different groups of bereaved adults. Nevertheless, further examinations of the Swedish TGI‐SR+ in diverse bereaved samples are warranted.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…These study characteristics may limit the generalizability of our findings to other groups of bereaved adults. However, it should be noted that the results found in the present study were comparable to the results of past validation studies using different samples (Kokou‐Kpolou et al, 2022; Lenferink et al, 2022), which appears to suggest that the TGI‐SR+ has similar psychometric properties across different groups of bereaved adults. Nevertheless, further examinations of the Swedish TGI‐SR+ in diverse bereaved samples are warranted.…”
Section: Discussionsupporting
confidence: 89%
“…Evidence for convergent validity was provided by showing strong positive correlations between DSM-5-TR and ICD-11 PG symptom levels as assessed with the TGI-SR+ and symptoms of PTS and depression. This aligns with the well-documented strong associations of PG symptoms with symptoms of these neighbouring disorders (Kokou-Kpolou et al, 2022;Lenferink et al, 2022; for reviews see Heeke et al, 2019;Komischke-Konnerup et al, 2021). Furthermore, strong positive associations were found between DSM-5-TR and ICD-11 PG symptoms and PG symptoms per Prigerson et al (2009).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…In case multiple losses are equally often on your mind and/or are equally stressful, please select one person while completing the questionnaire. Research demonstrated that the TGI-SR+ has good psychometric properties (Kokou-Kpolou et al, 2022 ; Lenferink, Eisma, et al, 2022 ). Cronbach’s alphas of the DSM-5-TR PGD items in this study were .93 at pre-VPS and .92 at post-VPS.…”
Section: Methodsmentioning
confidence: 99%